Knowledge and Attitude about Leprosy among Indian Dental Students in Faridabad - Jain, Meena (J Clin Diagn Res, 2016)
INTRODUCTION: Role of dentists in prevention and sustainable care of leprosy is known. Changing leprosy scenario has led to requirement of change in leprosy education. However, knowledge and attitude of dental students on leprosy remains unknown. AIM: Hence a study was conducted to assess knowledge and attitude of dental students about Leprosy. MATERIALS AND METHODS: A questionnaire based, cross-sectional survey was conducted among 350 undergraduate and the postgraduate dental students of two dental colleges in Faridabad, India. The score for knowledge ranged from 0 to 16 and scores for attitude ranged from 0 to 26. These scores were further coded as poor, fair and good. RESULTS: Mean knowledge score for the sample was 7.64±3.23. A total of 32.29% participants were under poor knowledge category; 57.42% had fair knowledge about Leprosy while 10.29% had good knowledge. Mean attitude score was 15.5 ± 5.98. A total of 30.57% had poor attitude scores, 42.57% had fair scores while 26.86% had good attitude scores. Univariate analysis showed year of training to be a significant predictor for knowledge level (t=7.12; p<0.001). CONCLUSION: The results indicate need for three important changes towards Leprosy in Dentistry. These changes are need for incorporation of leprosy education in Dentistry, need for incorporation of problem based as well as evidence based learning in Dentistry integrated with general health and need for reestablishing public health programs for Leprosy utilizing dental workforce.